SPE Annual Technical Conference and Exhibition 1979
DOI: 10.2118/8204-ms
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations Of The Combined Effects Of Wellbore Damage And Partial Penetration

Abstract: There is considerable disagreement in the literature concerning the interpretation of wellbore damage (the skin effect) in partially completed wells. The skin factor is composed of two components, one of which is indicative of actual formation damage and the other of which results from an additional pressure drop due to the partial completion. The skin factor measured in a buildup test does not reflect the simple sum of these two components. Rather, the effect of the actual damage is accentuated by the partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For the purposes of candidate selection, the following skin components, as derived by various authors, [31][32][33][34][35] are evaluated and provided after the following equation. Detailed definitions of each skin term are provided in Table 1 (Page 7).…”
Section: Phase 1-candidate Selection and Damage Identificationmentioning
confidence: 99%
“…For the purposes of candidate selection, the following skin components, as derived by various authors, [31][32][33][34][35] are evaluated and provided after the following equation. Detailed definitions of each skin term are provided in Table 1 (Page 7).…”
Section: Phase 1-candidate Selection and Damage Identificationmentioning
confidence: 99%
“…To perform a similar verification in case of partially penetrating well we used pseudo-skin due to partial penetration proposed by of Saidikowski. 10 Figure 2 displays the comparison of the obtained results. As it seen from Figure 2, the match of the values predicted by the model and the analytical solution for radial flow (100% penetration) is perfect.…”
Section: Modeling Of the Transient Pressure Distribution Aroundmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Brons and Marting 1 observed that the partial penetration generates a pseudo damage reducing the well productivity. The others have confirmed that an additional pressure drop is created by the partial penetration effect.…”
Section: Introductionmentioning
confidence: 99%
“…The others have confirmed that an additional pressure drop is created by the partial penetration effect. [2][3][4][5][6][7][8] The additional pressure drop is measured in terms of partial penetration pseudoskin, . Graphical results pp s 1 , analytical solutions 2,3 , numerical solutions 4,5 , and empirical equations [6][7][8] have been proposed to compute the pseudoskin resulting from partial completion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation